PENGENDALIAN KUALITAS SPANDEK DENGAN METODE TAGUCHI UNTUK MENGURANGI KECACATAN PRODUK - Supriyono, Supriyono; Suryanto, Dwi (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
PT. Rajawali Perkasa Metalindo is an iron distributor that sells various kinds of iron: Hollow, Pipe, CNP, UNP, Plate, Iron Accessories and produces mild steel such as Spandek and Bondek. In this study discusses what are the most important factors in the analysis of holes in Spandek based on the calculation of response tables by the Taguchi method. The results of the Taguchi method can be described as follows: After the conclusions are obtained, the questionable factors of control factor A with a factor of level 2 (Medium level machine speed of 240 ms - ^ 1), control factor B with a factor of level 1 (Thick Coil level Low is 0.30 mm, and control factor C is with level 1 factor (Low Level Cut Blade Distance is 4 bar). While the results of Anova data processing obtained values of the Anova test results include: Factor A has a calculated F value = 6.17 and F table = 3.40, Factor C has a calculated F value = 11.38 and F table = 3.40 and Factor B has a calculated F value = 10.42 and F table = 3.40.